La imputabilidad de la persona con trastorno mental transitorio ante el juzgador - Terán Arellano, Kelly Mishel (2024)
The accountability of an individual with Transitory Mental Disorder (T.M.D.) poses a complex relationship between mental health and criminal responsibility. This disorder, associated with a temporary mental disorder, affects the individual's will, generating a momentary state of unconsciousness that may lead to the commission of actions without full awareness of their rights. In the legal context, this significantly impacts the determination of accountability when committing a crime. Although Article 36 of the Comprehensive Organic Criminal Code (COIP) does not detail the procedure for cases of transient mental disorder, an objective interpretation is adopted. According to this interpretation, despite the diminished capacity to comprehend the unlawfulness of the conduct, criminal responsibility is upheld, with a reduction of one-third of the minimum penalty. However, the lack of a precise definition leads to ambiguities. Therefore, to determine the degree of accountability, it is essential to examine the elements that must be presented before the judge, who will be responsible for assessing objective accountability when applying the penalty in the case. The research focuses on analyzing the elements of the process that will be presented before the judge to determine the accountability of an individual with Transitory Mental Disorder when imposing a penalty. The primary objective is to ensure a fair and consistent application of the law, taking into account the protection of society and the rights of those affected. The investigation explores the social phenomena influencing the understanding of the unlawfulness of behavior and how the legal system addresses these situations, providing a detailed insight to enhance the interpretation of accountability in the context of T.M.T. by offering clearer and more coherent guidelines at the intersection of mental health and criminal responsibility.